Improving Sales Volume To Maintain Business Sustainability Through Digital Marketing And Financial Literacy For Msmes In Cilodong, Depok - Nur Fitri Dewi (Neo Journal of economy and social humanities, 2023)
Along with the dynamics of MSMEs in Indonesia, their development faces several problems related to whether the sustainability of MSMEs in Indonesia can be tested in the long term. The aim of this research is to determine the influence of digital marketing and financial literacy on sales volume and its impact on business sustainability in MSMEs in Cilodong, Depok, West Java. The population of this study is MSMEs Cilodong District, Depok City, West Java. The data collection method was a questionnaire distributed to 60 samples of MSMEs in Cilodong, Depok. The collected data was processed using SPSS 27.00 with t test and Path Analysis. The research results show that digital marketing and financial literacy have a positive effect on sales volume. Digital marketing and financial literacy also have a positive influence on business sustainability, both directly and indirectly, mediated by sales volume. Apart from that, sales volume has a direct effect on business sustainability. The results of this research can be useful for MSMEs as input and consideration in determining strategies, especially regarding Sales Volume and Business Sustainability of MSMEs in Cilodong, Depok.